2013
DOI: 10.1371/journal.pone.0078924
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes : An Independent Risk Factor for Tuberculosis: A Nationwide Population-Based Study

Abstract: ObjectiveTuberculosis continues to be a major global health problem. We wanted to investigate whether Type 2 diabetes was a risk factor for tuberculosis in an Asian population.MethodsFrom Taiwan’s National Health Insurance Research Database, we collected data from 31,237 female patients with type 2 diabetes and 92,642 female controls and 32,493 male patients with type 2 diabetes and 96,977 male controls. Cox proportional hazard regression was performed to evaluate independent risk factors for tuberculosis in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 20 publications
(23 reference statements)
2
22
0
2
Order By: Relevance
“…According to a systematic review, among cohort studies, people with DM had an approximately 1.16–7.83 times greater risk of developing TB than did people without DM . Previously, one population‐based study revealed that diabetic Taiwanese patients had a relative risk of 1.3 for developing TB after adjustment for confounding factors . The results of our nationwide population‐based cohort study showed that patients with T2DM are at a significantly higher risk of developing TB after adjusting for confounding factors (aHR: 2.01; 95% CI: 1.80–2.25); our findings are consistent with the findings of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…According to a systematic review, among cohort studies, people with DM had an approximately 1.16–7.83 times greater risk of developing TB than did people without DM . Previously, one population‐based study revealed that diabetic Taiwanese patients had a relative risk of 1.3 for developing TB after adjustment for confounding factors . The results of our nationwide population‐based cohort study showed that patients with T2DM are at a significantly higher risk of developing TB after adjusting for confounding factors (aHR: 2.01; 95% CI: 1.80–2.25); our findings are consistent with the findings of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, most data provides support for DM preceding TB. All cohorts to date indicate that DM develops before TB, and those with further characterization of the DM patients suggest that it is not DM in itself, but rather, poorly controlled DM that increases TB risk (14, 27, 28) Cross-sectional studies also support the concept of DM preceding TB, with chronic DM patients (median 7 years) that present other DM complications prior to TB development (18, 20, 29). This highlights the missed opportunities for preventing TB among DM patients who have presumably been in contact for years with their healthcare providers.…”
Section: Epidemiology Of Tb-dmmentioning
confidence: 91%
“…This illustrates the complexity of studying DM as a risk factor for TB given the heterogeneity in DM populations worldwide with respect to their age, access to healthcare, level of glucose control, and the type and number of DM complications and medications. Furthermore, co-ocurrence of DM with other host characteristics can further synergize TB risk among DM patients, as suggested for DM plus smoking, micro and macro-vascular complications of DM, and even their social environment (12-14) This emphasizes the need for studies reporting a thorough characterization of DM and other host factors with multivariable analysis in order to reach reliable conclusions.…”
Section: Epidemiology Of Tb-dmmentioning
confidence: 99%
“…Three large population‐based studies had conducted stratified analysis by ethnicity, country of origin, indigenous status and TB incidence in country of origin. None of these studies showed an effect of these factors modifying the association between DM and TB .…”
Section: Resultsmentioning
confidence: 96%